Analysis of Security Projections in the Reconciliation of Relations between Iran and Saudi Arabia - Akbar, Alwi; Machmudi, Yon; Fikri, Naufal; Mahendra, Yusril Ihza (Intermestic: Journal of International Studies, 2025)
With ideological battles, defense rivalries, and the rise of proxies in regional countries, Saudi Arabia and Iran represent the pinnacle of rivalry in the Middle East region. Both countries have had a history of volatile conflict escalation over the past few decades, culminating in Iran's severance of diplomatic relations with Saudi Arabia in 2016. After many years, they finally agreed to reconciliation and improvement of diplomatic relations, particularly in the field of security. China has played an important role as a broker in this reconciliation process. This has shifted the role of security policy, which has long been dominated by the United States. This paper aims to analyze how the Saudi Iranian rapprochement affects the stability of the Middle East Security Complex. We use the Regional Security Complex Theory (RSCT) of Barry Buzan and Ole Wæver to analyze and project the dynamics of the relationship between these two countries on the security of the Middle East region. The research methodology uses an exploratory qualitative approach to broaden the scope of the analysis of the security implications of the Middle East, after the improvement of the relationship between these two countries.